REVIEW OF ISLAMIC LAW ON THE STATUS OF MOSQUE IMAMS AS ZAKAT MANAGERS IN TIROANG DISTRICT, PINRANG REGENCY (Analysis of MUI Fatwa No. 8 of 2011) - Muh. Aidil Fitra, Aidil; M. Thahir Maloko; Mahmudah Mulia Muhammad (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2025)
Abstract The management of zakat in Tiroang District, Pinrang Regency is managed by the Imam of the mosque and in its management does not have legality from the government, as explained by Madeali that